Russia-Ukraine conflict and Malaysian palm oil: An analysis of market impacts and public sentiment. - Azlizan Mat Enh; Hasrina Mustafa; Fahri Ahmed (PLoS ONE)
The Russia-Ukraine conflict, which began in February 2022, has significantly impacted global commodity markets, particularly the Malaysian palm oil industry. This study examines the effects of the conflict on key market indicators-price, production quantity, oil extraction rate, and exports-while also analyzing the role of public sentiment in shaping market dynamics. Using data from the Malaysian Palm Oil Board (MPOB) and online engagement metrics, a composite sentiment index was developed through Principal Component Analysis (PCA). The findings indicate that palm oil prices spiked sharply following the conflict due to supply chain disruptions and speculative trading, while production and extraction rates remained stable. Exports showed increased volatility, reflecting trade realignments and policy interventions. Public sentiment shifted from a fragmented geopolitical discourse to an economically driven narrative, strongly correlating with price fluctuations and concerns over supply chain stability. This study highlights the growing importance of sentiment analysis in understanding market behavior and provides insights for policymakers and industry stakeholders to mitigate the effects of geopolitical crises on the palm oil sector.